Utilization of agro-wastes to produce biofertilizer - Soh-Fong, Lim; Sylvester, Usan Matu (Springer Verlag, 2015)
The objective of this study was to develop a simple and cost-effective method to produce biofertilizer using agro-wastes. There were five types of agro-wastes being used in this study. They were wastes from watermelon, papaya, pineapple, citrus orange, and banana. Solid-state fermentation method was used to produce biofertilizer, which was then applied into vegetable plantation. Physical property tests were done on the plant samples of 5 weeks of age in order to determine the effectiveness of the biofertilizer. The results of the experiment showed that the plant samples treated with biofertilizer from watermelon, papaya, and banana wastes had promising physical characteristics. Other tests such as analyses of pH values and potassium content in the biofertilizers were also done in this research. It was found that watermelon biofertilizer had the highest pH value (5.15). The banana biofertilizer had the highest content of potassium with a content of 3.932 g K/L.